PENGARUH PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA KELAS IV SD GUGUS III - satriani satriani; Abd Hafid; Mujahidah Mujahidah; Kasma Kasma (Universtas Negeri Makassar, 2022)
The objektivw of this research is whether there is a significant effect of online learning on the learning achievement of fourth grade students of SD Gugus III, Awangpone District, Bone Regency by using a quantitative research model with a correlation design. Based on the results of descriptive statistical analysis, online learning has an average of 111.93 and a percentage of 86.32% in the very good category and the average student achievement has an average of 80.79 and a percentage of 81.94% in the very good category. Then based on the results of inferential statistical analysis, the tcount value (5.52729) is greater (>) the ttable value (1.66365) at a significance level of 5%. Thus H0 is rejected and Ha is accepted. The conclusion is that there is a significant influence between the influence of online learning on the learning achievement of fourth grade students at SD Cluster III, Awangpone District, Bone Regency.